KAJIAN FEMINISME RADIKAL DALAM NOVEL KEINDAHAN DAN KESEDIHAN KARYA YASUNARI KAWABATA - Andharu, Devito; Widayati, Wahyu (FKIP - Universitas Dr. Soetomo Surabaya, 2018)
The Purpose of this research are to describe a feminism in Keindahan dan Kesedihan Novel by Yasunari Kawabata.This research is a qualitative descriptive. The object is psychoanalysis from Keindahan dan Kesedihan, novel by Yasunari Kawabata. Data collected by using close reading technic: read, scan, and quote. Data validity use triangulation technic. Data analized by semiotic mode of reading. Analysis result is shown in terms of feminism, the role of Otoko and Keiko is the main character in Keindahan dan Kesedihan novel that she is a s lesbian. Lesbian is an example of the uprising at the radical feminism. But after reviewing the whole of Keindahan dan Kesedihan novel be able to conclude that the figures of Otoko are not included in radical feminism. Otoko chose to become lesbian with Keiko after the she met with the students painted Keiko. Otoko choice of life lived as a lesbian is to keep the sacred vision in maintaining its love for Oki. In contrast to Otoko, Keiko chose to become lesbians based on hate with men. Keiko found men always give the suffering of women. Keywords :Feminism, Novel